Design & Development of 3 Degree of Freedom Robot Controller - Min Chai, Sheng Le (Universiti Teknologi PETRONAS, 2016)
Robotic technology had existed for more than one century in our modern society. The existence of robot had brought the society with many progressive improvement in many field. In the current modern world industry, robotic technology played a very important part in daily working activities as well as industrial performance of a company. There are multiple approaches for solving the robot kinematics algorithm that had existed in the current industry such as forward kinematics, inverse kinematics and Denavit-Hartenberg Matrix Representation. As for this project, the robot platform will be control by using forward kinematics, inverse kinematics and Denavit-Hartenberg Matrix Representation to produce the robot controller as well as the control strategy. The robot controller consist series of robot controller and motor driver that will be communicating with the main controller.